SOME CATIONS MOVEMENT IN CALCAREOUS SOIL COLUMNS UNDER EFFECT OF SALINE WATER MIXED WITH HUMIC ACID - & et al., Al-Hadethi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
A laboratory experiment was conducted to study the impact of humic acid with different levels of saline water on the movement of Sodium, Calcium and Magnesium, and the kinetics of Sodium adsorption ratio in calcareous soil with a texture clay loam using the mixing displacement techniques. The soil was taken from the surface layer (0-30 cm), air dried and passed through a 2 mm diameter sieve. It was filled in columns of polyethylene. A fixed column of water was placed above the surface of the soil column of different salinity water (0.72, 3.00, 5.00 and 7.00 dSm-1), in accordance with humic acid levels of 0.00, 0.25 and 0.50 g L -1. The process of washing and collecting leachate continued daily. The amount of Sodium, Calcium and Magnesium in the water filtered over time. The results showed that the amount of Sodium released increases with the levels of added humic acid and any levels of saline water used. The amount of Calcium and Magnesium released decreases with time and increases the added levels of the humic acid and any levels of saline water used. Diffusion equation is the best equation described the movement of salt.